O que há de errado com o mundo: uma análise retórica dos paradoxos de Chesterton - Santana, Samuel Cardoso (2015)
The style of the English writer Gilbert Keith Chesterton (1874-1936) is marked by the presence of the paradoxes, used in the argumentation, persuasion and stylistic. By this rhetoric, Chesterton debated with great intellectuals from his time such as George B. Shaw and Bertrand Russell. The corpus analyzed in this work is O que há de errado com o mundo. It‘s an example of Chesterton‘s rhetoric, it brings marcs of the writer‘s maturity, it‘s a book of debate, on which stands out with the rhetoric form. The book was published in 1910 and had a recent translation to Portuguese by Luíza de Castro Monteiro Silva Dutra. There are many essays of polemical themes of his time. All argumentation is marked by the irony, uncovered by paradoxes, beyond the constant use of metaphors that permits an appreciation for many kinds of readers. The objective of this work is to identify the rhetorical elements present on the paradoxes used on the work, identify the pathetical elements, by an argumentation‘s analysis, trying to find sophisms. The paradoxes used are ironic and make a dialog with the auditory, who sets himself on the writing by the pathetical reactions aroused. By Meyer (1994, 2000, 2007a, 2007b), will be make a verification of the emotions evoked by Chesterton‘s paradoxes; with Schopenhauer (1997, 2001, 2003, 2005) and Aristóteles (2010, 2011), the possible sophisms. Perelman and Olbrechts-Tyteca (2005), Lausberg (1972), Reboul (2004), Beristáin (1995) and Fiorin (2014) treat the figures necessary for the approach of many aspects that make the construction of the paradoxes, like irony, antithesis, allegory. The methodology applied parts from the lecture and detection of the paradoxes; by a qualitative-quantitative study, it is performed the analysis of the paradoxes finded, classifying then by the form and the structure, by the objective and the pathetical devices. The analysis allowed to observe that Chesterton used the paradoxes like attack‘s arguments with major frequency than like refutation forms form the opponent‘s thesis, which was evidenced by the recurrence of the negative passions raised on the auditory by relation to the opponent and to the recurrence on the use of irony. As the sophistrie, Chesterton recurred to only one along the corpus analyzed. Key words: paradox; rhetoric; Chesterton; rhetorical figures.